THE CONCEPT OF EXTRACTIVE WASTE - Nawrot, Filip (Review of European and Comparative Law, 2017)
The analysis of the concept of extractive waste is the main point of this paper. This matter is interesting because it is connected both with the geological and mining law as well as with the “waste law” . In the first part of the paper some remarks about the definition of waste from the Act on Waste are made . In this part the relation between the definition of waste and the definition of extractive waste, which can be found in the Act on Extractive Waste, is also presented . Afterwards other concepts used in the definition of extractive waste are analysed . Some exceptions in which provisions of the Act on Extractive Waste do not apply are discussed in the last part .